Reconfigurable SOI-MOSFET: Past, Present and Future Applications - Rangel, Ricardo Cardoso; Sasaki, Katia Regina Akemi [UNESP]; Martino, Joao Antonio (Journal of Integrated Circuits and Systems, 2022)
This paper presents a historical analysis of recon-figurable field effect transistors (RFETs). History shows the naturalness of its development from the evolution of integrated circuits (ICs) technology. Next, its operating principles are detailed to further study the variety of structures proposed in the specialized literature. Among these structures, the Back Enhanced SOI MOSFET (BESOI MOSFET) has been studied in detail, which stands out for its simplicity of fabrication and the possibility of integration with conventional technologies. TheBESOI MOSFET is used to present proofs of concept for RFET applications such as: reconfigurable digital circuits, light sen-sor, permittivity-based biosensor and charge-based biosensor. The latter may allow, for example, obtaining a glucose sensor. Finally, future perspectives of applications of RFETs are pre-sented, as in systems of protection of the intellectual property of ICs.
Keywords: Biosensor; Electrostatic doping; Reconfigurable-FET; Sensor; SOI-MOS